Large lateral sized two-dimensional Cu2-xS nanoplates formed by Ostwald ripening - Wang, A.; Hu, X.; Wang, F.; Chen, W.; Pang, Y.; Javaid, S.; Chen, D.; Li, X.; Staaden, L.; Jia, Guohua (Elsevier BV, 2019)
Large lateral sized two-dimensional (2-D) colloidal nanocrystals with a uniform thickness are highly desired but difficult to prepare. Herein we demonstrated that colloidal copper (I) sulfide (Cu1.75S) nanoplates with an large lateral dimension, i.e. 200 nm to 1 µm, can be successfully produced from small Cu2-xS nanoplates via an Ostwald ripening process. The availability of the large lateral sized Cu2-xS nanoplates produced through this approach not only sheds light on the construction of 2-D nanostructures of other systems but also provides a platform for the cation exchange reaction to generate a variety of 2-D nanoplates with large lateral dimensions.